2014
DOI: 10.1587/elex.11.20140711
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, design and experimentation of series-parallel LCC resonant converter for constant current source

Abstract: This paper presents the topology selection, design and experimentation of LCC resonant converter with isolated transformer for constant current source. Possible LCC topologies are classified based on the number of elements contribute to the dynamical change in energy. Topologies suitable for constant current source are selected based on the source/sink combination. The current gain transfer function is obtained for the selected topologies using sine-wave approximation method. The LCC resonant converter behavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This technology has now emerged as an essential application in diverse fields such as autonomous underwater vehicles (AUVs), unmanned aerial vehicles (UAVs), and electric vehicles (EVs) [1,2,3,4,5]. Current research efforts on WPT systems have mainly centered on studies of converter topologies [6,7], compensation topologies [8,9], coupling mechanisms [4,10,11], and control strategies [12,13]. Among these areas of inquiry, the investigation of converter topologies represents a significant facet of WPT technological advancement.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has now emerged as an essential application in diverse fields such as autonomous underwater vehicles (AUVs), unmanned aerial vehicles (UAVs), and electric vehicles (EVs) [1,2,3,4,5]. Current research efforts on WPT systems have mainly centered on studies of converter topologies [6,7], compensation topologies [8,9], coupling mechanisms [4,10,11], and control strategies [12,13]. Among these areas of inquiry, the investigation of converter topologies represents a significant facet of WPT technological advancement.…”
Section: Introductionmentioning
confidence: 99%
“…Various topological techniques [9] and control strategies [10,11], are studied with the purpose of achieving a constant current. Complex control methods for wireless systems are used to regulate output under different load conditions [12][13][14]. High energy losses, the need to use sensors, and large space to build can be the most important limitations of these methods [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The current source property is obtained without using any feedback loop and only by configuring the resonant tank. In [6], all possible combinations of the resonant tank with three resonant elements have been analysed. It is shown that a particular combination of the LCC resonant tank behaves as a constant current source at 1:4x n (where x n is the normalised switching frequency).…”
Section: Introductionmentioning
confidence: 99%